The Evolution of Liberation Theology in South Africa - Walshe, Peter (Journal of law and religion, 1987)
Before examining more recent developments, a historical perspective is helpful in coming to understand the emergence and evolution of liberation theology in South Africa. This perspective establishes the contrasts between the passivity of the churches - their flaccid social and political witness - during the first six decades of this century and what followed after the shootings at Sharpeville in 1960.By the late 19th century, the white Dutch Reformed Churches (DRC) were intimately associated with the rise of Afrikaner nationalism and provided the initial institutional structure around which the volk gathered. As the 20th century unfolded, an Afrikaans language movement, the Afrikaner National Party, a secret society—the Broederbond (Brotherhood), separate volk schools, various welfare organizations and the Federation of Afrikans Cultural Organizations all helped to strengthen the white nationalist movement that was to capture the South African state in 1948. Afrikaner corporations helped to consolidate that power—SANLAM, VOLKSKAS and Federale Mynbou being pre-eminent. Afrikaner leadership was nurtured within the white trade union movement. Having gained control of the state, Afrikaners also came to dominate the civil service as well as the extensive parastatal sector of the apartheid economy. They established their ascendancy in the military and police. As Dr. Malan put it in 1938 when speaking at the centenary of the Battle of Blood River: "The Trekkers received their task from God's hand. They gave their answer. They made their sacrifices. There is still a white race. There is a new volk." A decade later that nation had come to power.